Rice suitability mapping using the analytic hierarchy process approach in a river catchment - N. Robertson; B. Oinam (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Land suitability analysis is a technique of attaining optimum utilization of natural available land resource. This study is the first attempt to map the potential rice suitability zone besides the existing rice cultivation zone in Imphal-Iril River catchment. The overriding objective of this study is to identify the land suitability potential zones for rice crop cultivation. The study was carried-out in Imphal-Iril River catchment, Manipur, India.METHODS: The suitability analysis was carried-out based on soil, climate and topographic parameters as the input variable using integrated geographical information system and analytic hierarchy process, a multi criteria decision based approach. To compute criteria weight for various suitability classes, pairwise comparison matrix was applied using analytical hierarchy process and the resulting weights were used for assigning criteria ranking.FINDINGS: The study result indicates that the major section of high and moderate potential suitability zones of rice is concentrated in the flatter valley regions of the catchment.  The result also indicates that there is 79.15 km2 of the area which can be potentially cultivated other than the existing agriculture cover. The major patches of such zones are found in the north-western portion of the valley region in the catchment.CONCLUSION: This study clearly indicates, the potential zones lying in the foothills in the north-western which are still not under the agriculture cover have the potential to be cultivated as per the model result. The model result clearly indicates the potential of geographical information system integrated with analytical hierarchy process technique can be utilized to decide the weights of each individual parameter using experts’ opinions which can serve as a versatile tool to carry-out such kind of analysis which can aid policy makers.